Superior trans‐septal approach for minimally invasive mitral valve surgery via right small thoracotomy. Issue 8 (24th June 2019) - Yamazaki, Masataka; Yoshitake, Akihiro; Takahashi, Tatsuo; Ito, Tsutomu; Kimura, Naritaka; Shimizu, Hideyuki
Abstract: Minimally invasive mitral valve surgery (MIMVS), despite its challenges, is not a rare procedure. However, MIMVS via a right small thoracotomy must be performed using long‐shafted surgical instruments and thoracotomy instruments specialized for minimally invasive cardiac surgeries. We have performed 12 cases of MIMVS via right small thoracotomy using the superior trans‐septal approach and secured a surgical visual field that easily allows a finger to reach the mitral valve annulus without using special instruments for minimally invasive cardiac surgery. We named this technique the "drawer‐case technique." In conclusion, MIMVS via right thoracotomy using the superior trans‐septal approach can be performed easily and safely, similar to mitral valve surgery performed via median sternotomy.